Who broke Lincoln's thumb? - Roy, Ron, 1940- (Roy, Ron, 1940- Capital mysteries, 2010)
When they discover that one of the thumbs has been broken off the statue in the Lincoln Memorial, KC and Marshall set out to learn what happened and restore the thumb before a ceremony honoring the sculptor.